A produção e a gestão da população de rua: A trajetória de Luciene - Martinez, Mariana Medina; De Paula Pereira, Luiz Fernando; Barbosa, Aline Ramos [UNESP]; De Oliveira, Luciano Márcio Freitas; Do Prado Pazzini, Domila (My University, 2014)
The article Production and Management of the Street Population: Luciene's Story presents the story of a transvestite expelled from where she worked as a prostitute by the local authorities and put into a municipal social care program. One year later she was considered part of the street population. To reconstruct the story and its analytical offshoots, we used a periodical snippet of one year of field research. Our intention was to critically analyze the modes of production and public management of contemporary marginal populations; the role of care policy users in the production and updating of the care network; and the formation of a non-institutional network, composed of street dwellers in public spaces.
Production and management of the street population: Luciene's story
Keywords: Homeless population; Marginality; Public policy; Social welfare; Subjectivity